ID: 72. Issue 4 (April 2016) - Chen, J; Sysol, JR; Shioura, KM; Singla, S; Yamamura, H; Yamamura, A; Reddy, V; Torres, J; Sridhar, A; Tang, H; Yuan, JX; Garcia, JG; et al.
Abstract : Rationale: We have previously shown that Nampt, which regulates intracellular NAD levels and cellular redox state, regulates histone deacetylases and inhibits apoptosis, is significantly upregulated in patients with pulmonary arterial hypertension (PAH). The aims of this study were to determine (1) whether Nampt +/− mice are protected from hypoxia-mediated pulmonary hypertension (HPH), (2) whether pharmacological inhibition of Nampt could attenuate monocrotaline (MCT)-induced pulmonary hypertension (PH) in rats. In addition, we hypothesized that Nampt secreted from pulmonary artery endothelial cells (PAECs) or overexpressing Nampt in pulmonary artery smooth muscle cells (PASMCs) may promote PASMC proliferation via upregulation of calcium signaling pathway, which plays a role in cell proliferation and vascular constriction. Methods: Nampt +/− mice and their WT siblings (male, 7-wk old) were exposed to a hypoxia chamber with 10% O2 for four weeks. Male Sprague-Dawley rats (n=6 per group) received one dose of MCT (60 mg/kg), IP. They were administrated with FK866 (an inhibitor of Nampt enzymatic activity) (2.5 mg/kg, IP, twice daily for 2wks) two weeks after MCT. Right ventricular systolic pressure (RVSP) was determined with a pressure transducer catheter. The right ventricle: left ventricle+septum (RV/LV+S) ratio was calculated. In a cell culture model, hPASMCs were stimulated with recombinant Nampt (25 mg/ml) for 6 hrs and 48 hrs. [Ca 2+ ]cyt was measured in PASMC loaded with flura-2/AM (4mM) in a fluorescence microscope and cyclepiazonic acid (CPA, a specific Ca 2+ -ATPase inhibitor) was used to induce store-operated calcium entry (SOCE). In addition, BrdU assays were conducted to examine rNampt or overexpressing Nampt can promote PASMC proliferation or Nampt secreted from PAECs isolated from PAH patients stimulates more PASMC proliferation than from healthy controls. Results: Administration of FK866 reversed established PH (RVSP [mm Hg] 19.77±0.80 [control] vs 51.24±4.35 [MCT] vs 34.45±3.49 [MCT+FK866], p<0.05 ) and RVH (0.25±0.0013 vs 0.60±0.019 vs 0.43±0.022, p<0.01). In PASMCs, short (6 hrs) and long (48 hrs) treatment with recombinant PBEF enhanced SOCE which is involved in sustained pulmonary vasoconstriction and PASMC proliferation. rNampt promotes PASMC proliferation in a dose dependent manner. PAECs from PAH patients secreted more Nampt which stimulates more PASMC proliferation compared to healthy controls. Overexpressed Nampt promotes PASMC proliferation. Inhibition of Nampt via FK866 attenuates rNampt-, Nampt overexpressed or PAEC-secreted Nampt – mediated PASMC proliferation. Conclusion: Inhibition of Nampt attenuates hypoxia-mediated PH in mice or MCT-induced PH in rats. Nampt may play a role in vascular remodeling via regulation of calcium signaling pathway. These data suggest that Nampt inhibition could be a potential therapeutic target for PH.